Produk Olahan Berbahan Dasar Ikan Tongkol (Euthynnus Affinis) di Lampulo Banda Aceh: Processed Skipjack Tuna (Euthynnus affinis) Products in Lampulo, Banda Aceh - Ferijal, Teuku; Jayanti, Dewi Sri; Agustina, Raida; Mechram, Siti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Gampong Lampulo in Banda Aceh has excellent potential as a fish trading hub, particularly for skipjack tuna (Euthynnus affinis), a commodity of high economic value. However, skipjack tuna is highly perishable and often results in significant waste during peak harvest due to limitations in processing and packaging facilities. This community service program aims to enhance the knowledge and skills of local fishermen in processing skipjack tuna into value-added products that can improve their economy. The methodology applied includes training sessions consisting of lectures, group discussions, demonstrations, hands-on practice, and the introduction of appropriate technologies such as solar dryers, oil presses, liquid smoke as a preservative, and hand sealers for hygienic and attractive packaging. The results of this activity show that participants experienced significant improvement in practical skills, enabling them to produce processed products such as shredded fish (abon), smoked fish, and keumamah. This program successfully reduced post-harvest waste, extended product shelf life, and increased the market value of local fishery products. In conclusion, the program empowered fishermen with efficient and sustainable processing techniques and opened opportunities for them to expand their market. However, further assistance in marketing strategies, packaging design, and obtaining product certifications is needed.